New species of pinnotherid crabs from Southeast Asia and Papua New Guinea (Crustacea: Decapoda: Brachyura) - Ahyong, Shane T.; Ng, Peter K.l. (Zootaxa, 2020)
Three new Indo-West Pacific species of pinnotherid crabs are described, one each of Arcotheres, Buergeres and Nepinnotheres. Arcotheres pollus, described from Paway Island, Mergui Archipelago, is most similar to A. boninensis (Stimpson, 1858), A. pernicola (Bürger, 1895) and A. purpureus (Alcock, 1900), sharing a transversely ovate carapace and long, slender, almost styliform dactyli of P4 and 5 that are about twice the length of those of P2 and 3. Buergeres choprai, described from Papua New Guinea, is most similar to B. deccanesis (Chopra, 1931) from eastern India but differentiated by segment proportions and setation of the walking legs. Buergeres tenuipes (Bürger, 1895) is synonymised with B. ortmanni (Bürger, 1895), which is also reported for the first time from Indonesia. A male of an undetermined species of Buergeres from the Philippines, possibly B. ortmanni, is figured and described, documenting the gonopod morphology in Buergeres for the first time. A key to the species of Buergeres based on females is provided. Nepinnotheres fulvia sp. nov. is also described from Papua New Guinea, and resembles N. cardii (Bürger, 1895) from the Philippines and Malaysia but can be distinguished by features of the chelipeds and maxilliped 3.